Smooth muscle actin and s100p on non germinal centre diffuse large B cell lymphoma are adverse prognostic factors: pilot study - Abd El All Howayda (BMC, 2007)
Abstract Introduction The expression of smooth muscle actin (SMA) and s100p has been identified on an aggressive retro-orbital diffuse large B cell lymphoma (DLBCL) <abbrgrp>1</abbrgrp>. Aim To assess the prognostic significance of immunohistochemical (IHC) expression of SMA and s100p on DLBCL. Materials and methods Twenty nine cases diagnosed as DLBCL were first classified into germinal centre (GC) B cell like and non GC origin either activated B cells (ABC) or type 3 based on their immunoreactivity for CD10, bcl-6 and Mum-1. Bcl-2 and MIB-1 as adverse prognostic factors were assessed. SMA and s100p were evaluated and correlated with patients' clinicopathological characteristics. Results Eleven cases (37.93%) positive for CD10 and/or bcl-6 were classified as GC B cell like subtype, 7 cases positive only for Mum-1 as ABC subtype (24.14%), and 11 cases double positive or negative for bcl-6 and Mum-1 were considered as type 3 (37.93%). Nuclear and cytoplasmic SMA and s100p were expressed in 58.62% and 51.72% of cases respectively and were strongly associated with the non GC like phenotype (p < 0.001 for SMA and p < 0.01 for s100p). SMA and s100p were strongly related to each other (p < 0.001). SMA was closely associated with bcl-2 and MIB-1 (p < 0.01 and p < 0.025 respectively), while s100p was only associated with bcl-2 (p < 0.05). Conclusion SMA and s100p are expressed on non GC DLBCL and appear to be adverse prognostic factors. Future large studies evaluating their significance will be valuable to assess the different subgroups in clinical context. Lastly, this expression may lead to misdiagnosis of non hematopoeitic neoplasm if lymphoid markers are not included in the IHC panel.